Routledge handbook of modern Israel - Dieckhoff, Alain; Shread, Carolyn P. T (Routledge handbooks., 2013)
Israel is a country made up of contradictions. A lively democracy in a multicultural society but within a state promoting a strong national identity; a thriving economy in an unequal society; a culture open to modern trends but drawing on the Hebrew past and preoccupied with the Holocaust and the Arab-Israeli conflict; a sovereign member in the international arena, whose existence is still contested in the Middle East. The Routledge Handbook of Modern Israel provides a comprehensive profile of the intricacies of contemporary Israel, offering a unique, in-depth survey of the country.